Realisation of Iterative Algorithm of Six-Port Reflectometer on FPGA Using Logarithm Function - Zaichenko, O.; Zaichenko, N.; Galkin, P.; Golovkina, L. (My University, 2020)
The six-port reflectometer is an universal measurement device of microwave range for signal power and tract termination reflection coefficient definition. The definition of such tract and termination parameters is made by sensor signal processing. As processing algorithm can be used least squares estimation. The advantages of least squares estimation is accuracy. The condition of its use is redundandant sensor number. The least squares estimation feature is invers matrix computation. As to FPGA realisation of algorithm there are problems connected to matrix inversion. So the report is devoted to attempt to simplify six-port reflectometer sensor signal processing and to avoid inverse matrix computation.
Keywords: six-port reflectometer; processing algorithm; least squares estimation; logarithm